KAJIAN PENYELENGGARAAN PENDIDIKAN DI DAERAH PERBATASAN - Iskandar Agung (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
This study aimed to determine: (1) the condition of education practice, and (2) the condition of Nationality Insights of learners / students in the border area. The first aim is intended to describe the condition of education in the border area which is consists of the aspects of student input, infrastructure, human resource, education financing, curriculum, and learning outcomes. The study also attempts to analyze the effect of 5 aspects including students learning outcomes. The second one is intended to describe the condition of nationalism insight, then propose alternative ideas related to the effort of instilling and establishing the concept of nationalism to learners / students in the border area. The study obtained that the conditions of education and the nationalism insight of learners / students classified as inadequate, low, or poor. On that basis, there are some suggestions for improvement, namely: it is required to improve all aspects of education in the border area, related to the construction of school buildings, provision of learning facilities, fulfillment of textbooks, teachers’ abilities and skills, to build a residence (mess / home office) for educators and non-educator staff. Specifically in the establishment of nationalism insight of learners / students, it is required a deployment and expansion of the concept of nationalism education more intensively through intra-and extracurricular activities, along with the need to increase the role of local government, school principals, teachers, and supervisor as an agent or mediator of Nationality Insights.